Electric-field-induced rich magneto-absorption spectra of ABC-stacked trilayer graphene. Issue 98 (23rd October 2015) - Lin, Yi-Ping; Lin, Chiun-Yan; Chang, Cheng-Pong; Lin, Min-Fa
<x xml:space="preserve">Abstract</x> The magneto-optical spectra of ABC-stacked trilayer graphene are enriched by an electric field, providing a way to experimentally identify the stacking order of few layer graphene systems.